2020
DOI: 10.1088/1742-6596/1691/1/012139
|View full text |Cite
|
Sign up to set email alerts
|

The method for developing practice-oriented skills when studying the Control System Modeling course in the e-learning environment

Abstract: This article presents a model of a subsystem for performing practical tasks of an adaptive electronic learning resource (AELR) in the LMS Moodle environment. The authors consider the distinctive aspects of forming individual educational trajectories for the development of skills and abilities in studying the Control System Modeling course using the LMS Moodle instrumental apparatus. The paper presents an algorithm for developing the skills needed to perform the operations under study. The algorithm suggests st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The experience gained by Pozharkova (2020) in the AER implementation showed that the LMS Moodle e-learning platform contains tools a wide range for implementing individual educational trajectories and placing educational content, which makes organizing the educational process effective means in a virtual environment using the adaptive learning principles. At the same time, problems a number were identified that limit the LMS Moodle current versions use in the AER implementation, namely: a testing tool lack with counting the answers' number by category; data automatic loading impossibility (for example, test results) from third-party Internet resources, the student's work time automatic recording lack https://doi.org/ 10.…”
Section: Discussionmentioning
confidence: 99%
“…The experience gained by Pozharkova (2020) in the AER implementation showed that the LMS Moodle e-learning platform contains tools a wide range for implementing individual educational trajectories and placing educational content, which makes organizing the educational process effective means in a virtual environment using the adaptive learning principles. At the same time, problems a number were identified that limit the LMS Moodle current versions use in the AER implementation, namely: a testing tool lack with counting the answers' number by category; data automatic loading impossibility (for example, test results) from third-party Internet resources, the student's work time automatic recording lack https://doi.org/ 10.…”
Section: Discussionmentioning
confidence: 99%